IMPROVING VOCABULARY MASTERY USING SONG FOR THE SEVEN YEAR STUDENT OF SMP N 3 BATURETNO IN 2010/2011 ACADEMIC YEAR - Ridhowati, Handhika (2011)
This research aims at describing the implementation of song on teaching vocabulary for the seven year student of SMP N 3 Baturetno and describing the result of teaching vocabulary by using song to improve vocabulary mastery for the seven year student of SMP N 3 Baturetno. The problem of the study is how the implementation of teaching vocabulary by using song to improve vocabulary mastery and the result teaching vocabulary by using song. In this research, the data are derived from event, respondent, and document. There are three methods of collecting data namely: observation, interview, and document analysis. Song can improve vocabulary mastery. It is indicated by the score achievement of the second cycle that is higher than the score achievement of the first cycle. In the second cycle, there are more students who get more than 60. The writer also finds that the students are more active in the second cycle. They can answer the questions which give by the writer. Based on the research, the writer has come to the conclusion that using song is more effective to teach vocabulary for the seven year student because song can make the students enjoy the lesson and help them learn vocabulary easily.